Explaining the Inverse Association between Altitude and Obesity. (1st June 2020) - Merrill, Ray M.
Abstract : Purpose . To better understand the inverse association between altitude and adult obesity. Methods . An ecological study design was used, involving 3, 108 counties in the contiguous United States. Data were from several national sources, and assessment involved various statistical techniques, including multiple regression analysis. Results . Living in counties at higher altitude is associated with lower adult obesity. Compared with counties <500 meters, the percent of adult obesity decreases by 5.18% at 500–999 meters, 9.69% at 1, 000–1, 499 meters, 16.77% at 1, 500–1, 999 meters, 24.14% at 2, 000–2, 499 meters, and 35.28% at ≥2, 500 meters. After adjusting for physical inactivity, smoking, and other variables, corresponding decreases in adult obesity with higher altitude groupings are 3.87%, 5.64%, 8.03%, 11.41%, and 17.54%, respectively. Various mechanisms are presented as possible explanations for the association between higher altitude and lower obesity. In addition, altitude may indirectly influence adult obesity, primarily through its relationship with physical inactivity and smoking. In an adjusted regression model, adult obesity was most strongly associated with physical inactivity followed by adult smoking and then altitude. Together they explain 39.04% of the variation in adult obesity. After accounting for these variables, sunlight, precipitation, ambient air temperature, education, income, food insecurity, limited access to healthy foods, race, sex, and rural living explain an additional 4.68% of the variation in adult obesity. Conclusions . The inverse association between altitude and adult obesity remains significant after adjustment for several variables.